The relationship between science process skills and biology learning outcome - Mandasari, Fitri; Iwan, Iwan; Damopolii, Insar (Univeritas Papua, 2021)
The study aims to know the relationship between science process skills (SPS) and biology learning outcomes (LO) through inquiry-based learning in the class XI MIA Senior High School of State 01 Manokwari. The correlational method was employed in this research. The population in the study was students of class XI MIA High School at Manokwari. The samples in the study were class XI MIA 2 and XI MIA 4, with a total of 47 students. The sampling technique in this research was purposive sampling. Data collection techniques used tests and documentation. The hypothesis test used regression and correlation tests. The results showed a contribution of SPS to the biology LO through inquiry-based learning in the class XI MIA High School of Manokwari. The relationship of LO to biology student LO was 31%. The correlation coefficient is 0.557, indicating that the SPS level to the biology student LO was medium.